Diverse sources of resistance to Indian pathotypes of stem rust and leaf rust in durum wheat - Mishra A.N.; Sai Prasad S.V.; Shirsekar G.S.; Yadav S.R.; Kaushal K.; Dubey V.G. (Proceedings of the International Symposium on Genetics and breeding of durum wheat, 2014)
Stem rust (Puccinia graminis f. sp. tritici) and leaf rust (P. triticina) are among the most serious biotic stresses for durum wheat cultivation in India. Constant broadening of resistance base is necessary for maintaining effective and longer lasting rust resistance in view of the continued evolution of rust pathogens. Hence, Mendelian inheritance and extent of diversity for resistance were studied among five rust resistant durum wheat genetic stocks of diverse origin viz., ‘B 662’, ‘ED 2398-A’, ‘HG 110’, ‘IWP 5019’ and ‘Line 1172’. Of these, B 662, IWP 5019, and Line 1172 were derived from inter-specific hybridization involving crosses of different durum wheat genotypes with Triticum aestivum, T. turgidum var. dicoccum, and T. militinae lines, respectively. HG 110 was developed from an intra-specific (durum wheat / durum wheat) cross, while ED 2398-A was an Ethiopian durum wheat land race. The test pathotypes included 40A (62G29) and 117-6 (37G19) of stem rust, the former being the most predominant in nature and the latter being the most virulent one on Indian durum wheat; and the prevalent and durum-specific leaf rust pathotypes, 12-2 (1R5) and 104-2 (21R55). While seedling tests were conducted with the pathotypes 40A, 12-2 and 104-2, adult-plant studies were made with the pathotype 117-6. Analysis of the F2 populations and F3 families derived from the crosses of the aforesaid resistant stocks with three susceptible durum wheat varieties- ‘Motia’, ‘Malvi Local’ and ‘Sarangpur Local’ showed that resistance was governed by one or two genes. In all, four genes for resistance to the pathotype 40A, and eight genes each for resistance to 117-6 and 12-2 were identified among the five resistant stocks studied; while three genes for resistance to 104-2 were identified among B 662, ED 2398 A and IWP 5019, based on the allelic tests. Though the identity of these genes is not known, the ones for stem rust resistance are different from Sr2, Sr7b, Sr9e and Sr11, and those for leaf rust resistance are different from Lr23, the documented stem rust and leaf rust resistance genes commonly postulated among Indian durum wheat genotypes. Thus, the reported genetic stocks should contribute to enrich the gene pool in durum wheat improvement as diverse sources of resistance to stem rust and leaf rust.
International Symposium : Genetics and Breeding of Durum Wheat, 2013/05/27-30, Rome (Italy)